‘Father’ Imagery in 2 Corinthians 1-9 and Jewish Paternal Tradition - Myrick, Anthony A. (Tyndale bulletin, 1996)
The metaphor of ‘father’ played a significant role in the pastoral practice of Paul. There is evidence that a major line of Paul’s use of paternal imagery can be reliably traced back into the Old Testament and early Jewish tradition, namely the correction of his converts in 2 Corinthians 1-9. This finding suggests that Paul appears to owe much more to his ancient Jewish environment for his use of the paternal metaphor than has often been assumed, and sheds light on the nature and importance of Paul’s fatherly correction in his pastoral care of the Corinthian community.